What determined the uneven post 1975 development of Europe's southern regions? - Preliminary, short version (July 1998) - Gabriele Tondl (European Regional Science Association (ERSA), 1998)
Since 1975, the extent of catching-up has been very different between Southern regions. Starting from the proposals of growth theory, the paper wishes to show whether growth differences can be attributed to different endowment in human capital, differences in private or public investment level, in the speed of structural changes, and labour force participation. The econometric analysis is based on regional time series, compiled for the Spanish, the Greek and the Mezzogiorno's regions. To estimate the impact of the growth variables considered, a set of estimation methods, among them a GMM technique, is used. The results indicate that regional growth was very sensible to both human capital and investment. Therefore, dynamic development of Southern regions required improvement in education, an increase in public capital and a strong investment climate. In stagnating regions, indeed, policy efforts in these areas were rather unstable.
Keywords: 330